Kajian Ekologi Budaya Dalam Tradisi Nyabung Di Desa Adat Subagan, Kabupaten Karangasem - I Wayan Mardana Putra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The one of tradition which held until now in Desa Adat Subagan is Nyabung Tradition which is a part of Aci Purnama Sasih Kaulu. Nyabung Tradition be one of each tradition which relate with natural preservation, because on that tradition have value and hope from pople, especially Balinese Hinduism make pray for living peace like a Tri Hita Karana copcept. Because of that problem backround, the problem which be focus on this research is analysis of culture ecology on Nyabung tradition in Subagan Village, Karangasem Regency. Purpose of this research is to describe culture ecology on Nyabung Tradition in Subagan Village, Karangasem Regency. Theory of this research is sunctional structural. Result of this research is, there some ecologycal culture from Nyabung tradition such as Nyabung tradition have a relation with Tri Hita Karana concept and there's relation between Nyabung tradition with natural preservation. In skala way, natural preservation can see from controling from chicken population and how to take care chichken in order not to destroy our environment, in niskala way natural preservation by praying to God with some religion ceremony.